PEMBELAJARAN MATEMATIKA MELALUI PENDEKATAN ETNOMATEMATIKA PERMAINAN TRADISIONAL ENGKLAK PADA MATERI BANGUN DATAR - Agus Priyanto; Abdul Rauf Bimantara; Juandi Juandi; Ahmad Yani T (ADIBA : JOURNAL OF EDUCATION, 2022)
The value of mathematics contained in everyday life can be referred to as ethnomathematics. Ethnomathematics is learning mathematics found in cultural culture, ethnomathematics can also be used to apply mathematics in dealing with the natural environment and also in existing cultural systems. Indonesia has a variety of cultures, one of which is traditional games. There are many types of traditional games in Indonesia, one of which is the engklek game. The traditional engklek game is a game that many people know how to play and also in the engklek game there are elements of mathematics learning, for example the flat material contained in the engklek game. So the engklek game is found in mathematics learning, especially in the flat material.